International Brands & The Indian Consumer: A Study of Critical Success Factors with Special Focus on Select FMCG Brands - Memon, Sharif (Indian Journal of Marketing, 2011)
India is world's world's second largest consumer market and is the youngest country of the world in terms of age. This sort of phenomena makes India a hot market to cater for domestic as well as multi-national companies. Thus, all the global players across the globe eyeing the Indian market, this has resulted inmore options for the Indian Consumers to experience. The consumer at large is considered to be price conscious, which has been a myth that has been revealed in this study, that focuses on some select international brands in the consumable category where in eight pair to brands were selected based on the market share. This among the pair, one brand is successful as being having the highest market share among the International Brands in the same category whereas, another brand is less-successful in the same category. Here, the term less-successful is been used for low market share and does not imply failure, as its market share may boost up ( than the rival brand) in the future. Thus, this study explores the critical success factors for any foreign brand to succeed.